1994
DOI: 10.1183/09031936.94.07040651
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of increased epithelial lung clearance of DTPA in diffuse fibrosing alveolitis

Abstract: The aim of this study was to elucidate possible mechanisms of increased epithelial lung clearance in diffuse fibrosing alveolitis (DFA). We investigated the relationships between epithelial lung clearance as assessed by the clearance of aerosolized 99mTc-diethylene-triamine-penta-acetic acid (RC-DTPA), luminal alveolitis as assessed by bronchoalveolar lavage, and pulmonary function, in 30 nonsmokers with DFA. In 14 of these patients, RC-DTPA and lung function were determined before and during therapy with pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
2
7
0
3
Order By: Relevance
“…The specific mechanism of increased clearance times in FA is still unclear but has been thought to be secondary to the stretching of epithelial junctions in the alveolar wall as a result of fibrotic traction or lymphocytic infiltration [12,21]. The present findings support the hypothesis that the alveolar±capillary barrier is intact in cases of SSc with vascular disease and that the alveolar epithelial integrity is significantly impaired in matching patients with parenchymal fibrosis.…”
Section: These Results Show That the 99msupporting
confidence: 74%
“…The specific mechanism of increased clearance times in FA is still unclear but has been thought to be secondary to the stretching of epithelial junctions in the alveolar wall as a result of fibrotic traction or lymphocytic infiltration [12,21]. The present findings support the hypothesis that the alveolar±capillary barrier is intact in cases of SSc with vascular disease and that the alveolar epithelial integrity is significantly impaired in matching patients with parenchymal fibrosis.…”
Section: These Results Show That the 99msupporting
confidence: 74%
“…Therefore, we chose to use the half time of the epithelial lung clearance of aerosolized DTPA as the primary outcome for this trial. DTPA clearance predominantly assesses the permeability of the epithelium of the terminal respiratory units to solutes and is a sensitive index of lung inflammation in diffuse inflammatory lung disease (16)(17)(18), including acute minor pneumonitis after radiotherapy to the other lung (17). Measurements of DTPA clearance are influenced by smoking and position.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that inflammation in the lung contralateral to a pleurodesis might be detectable by 99m technetium-labeled DTPA lung scanning because this test is capable of identifying subtle lung inflammation in other settings (16)(17)(18)(19). This hypothesis led to the two randomized trials reported here.…”
mentioning
confidence: 97%
“…Confidence to change these management strategies is required. The studies by AGUSTI et al [13] and LABRUNE et al [18] in this month's issue of the Journal, taken together with other recently published articles on prognostic indicators, have shown that it is now possible to design appropriate studies to answer these important issues in early and advanced disease, and in treated and untreated patients. The important question, notably the difficult problem of prevention of deterioration, will require studies involving reasonably large numbers of patients, seen in specialist centres with an interest in diffuse lung disorders and a multinational, co-ordinated strategy.…”
Section: Editorialmentioning
confidence: 99%
“…In a recent retrospective study, abnormally rapid clearance of 99m Tc-DTPA at initial measurement was found to identify fibrosing alveolitis patients at higher risk of a decline in functional indices over the subsequent 3 yrs [17]. LABRUNE et al [18] set out to evaluate possible mechanisms of increased 99m Tc-DTPA clearance in fibrosing alveolitis and, by studying the effects of corticosteroid therapy, were able to demonstrate a reversible and irreversible component of rapid clearance. The observation of decrease in clearance in response to treatment is important and further emphasizes the value of clearance measurements in determining the need for treatment, particularly as the greatest rates of clearance were associated with the largest improvement in vital capacity in response to treatment.…”
Section: Editorialmentioning
confidence: 99%